Injection Molding of Mechanical Alloyed Ti-Fe-Zr Powder - (:unkn) unknown (SCIENCE PRESS BEIJING, 2012)
Powder injection molding (PIM) is a maturing technology that has proven most useful for the production of complex metallic and ceramic components of modest sizes. Considering the inevitable demand for cost-effectiveness in automotive applications, components manufactured from low-cost sponge titanium powder currently reflect the most advantageous economics among the available titanium powders. This study focuses on the injection molding of mechanical alloyed Ti-Fe-Zr alloys. Injection molded samples were produced by mechanical alloyed CP titanium powder and pure iron and zirconium. Mechanical alloyed powders were mixed to polymeric binder and molded as standard tensile bars. Molded bars were debinded by solvent and thermal debinding processes, under ultra pure argon atmosphere. Debinded samples were sintered at 1300 degrees C for 60 min. at high level vacuum (10(-5)mbar). After sintering, the performances of the sintered parts were characterized using tensile testing, hardness testing, optical microcopy (OM) and scanning electron microscopy (SEM). The strengths and weaknesses of the test conditions have been analyzed from the densification behavior, microstructure, and mechanical properties. Theoretical density, ultimate tensile strength and hardness of injection molded Ti powders increased with the additions of 5%Fe and 5%Zr.
Keywords: Powder injection molding; sintering; mechanical alloying; TITANIUM; MICROSTRUCTURE